ROLLING EFFECT ON DISSIMILAR FRICTION STIR WELDED AA5083-AA6061 ALUMINIUM ALLOY JOINTS - Selamat, N.F.M.; Baghdadi, A.H.; Sajuri, Z.; Junaidi, S.; Kokabi, A.H. (Journal of Advanced Manufacturing Technology (JAMT), 2020)
Friction stir welding (FSW) gives benefits to join un-weldable aluminium alloys, especially for joining dissimilar types of aluminium grade. The limit of FSW is thin materials will get affected due to forging effect from the tool shoulder. In this study, two types of aluminium alloys which are AA5083-AA6061 has been dissimilar welded in butt joint using FSW. The welding parameter used is 1000rpm and 100mm/min for rotation speed and transverse speed, respectively. Then, the post weld cold rolled (PWCR) has implemented to reduce 10%, 20% and 40% from the original thickness of samples. From the microstructure observation, there is defect free at all PWCR samples. The grain size in nugget zone has been reduced from 8μm to 5μm as the rolling is conducted at 10% and 40%, respectively. Further, the higher rolling percentage will improve the tensile strength. Therefore, the ultimate tensile strength is increased to 5%, 26% and 49% for rolling percentage of 10%, 20% and 40%, respectively. However, the elongation has been reduced to 24%, 55% and 68% as the rolling percentage improve. The tensile samples fractures outside the welding zone up to rolled 20%, and the fracture shift inside the welding zone when up to 40% of rolling percentage.